A controlled diaphyseal expansion osteotomy for the implantation of a wagner cone prosthesis in a stenotic femoral canal encountered in a polio limb: a case report of the technique - Kadam, Tushar S.; Desai, Mohan M. (International Journal of Research in Orthopaedics, 2020)
Dysplastic hips pose a significant technical challenge to arthroplasty surgeons. Such deformed hips might be encountered either in congenital and developmental conditions or as sequel of neuromuscular disorders (like poliomyelitis), following infections, or after childhood surgical procedures of the hip. The scientific literature, focussing on total hip arthroplasty (THA), for coxarthrosis in patients with residual poliomyelitis, is relatively rare. Several anatomical distortions seen in dysplastic femurs are described, one of which includes an undersized diaphysis with a stenotic medullary canal. We present a case of a 28 years old male with residual poliomyelitis who underwent a cementless THA for a non united transcervical neck of femur fracture. The patient had an extremely narrow medullary canal which posed a formidable difficulty in the procedure. This was overcome by a novel diaphyseal expansion osteotomy, which enabled the implantation of Wagner Cone prosthesis. This technique, which has hitherto not been described in the literature, can significantly facilitate the implantation of an appropriately sized stem in an undersized femur while at the same time ensuring a good long-term result.